The Theory of Monopolistic Quantity Discounts - Buchanan, James M. (Review of Economic Studies, 1952)
Journal Article The Theory of Monopolistic Quantity Discounts Get access James M. Buchanan James M. Buchanan Tallahassee, Florida Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 3, 1952, Pages 199–208, https://doi.org/10.2307/2295890 Published: 01 January 1952